The Development of research skills in project work for grade 11 students - Adekenova, A.N.; Ustinova, L.V.; Adekenova, U. (KSU Publ., 2017)
In 11 classes, in-depth study of subjects «Informatics», «Global perspectives» is expected. Throughout the course, the students carry out project work, therefore using different authors to develop research skills. The article demonstrates the personal experience of authors in writing projects and applying new approaches to teaching that contribute to the achievement of the goal. Authors cite fragments of the curriculum, a guide to writing a course work on the subject «Informatics», topics approving forms , an example of a lesson with elements of pedagogical tools and methods. Analyzing the feedback from the NIS alumni, they conclude that writing essays and course work develops students' high-level skills such as; critical thinking, analysis and assessment. Also, the obtained school experience helps in writing similar works in higher educational institutions. Students acquire competitive skills, unorthodox thinking and active personalities. The study of the subject «Global perspectives» makes the younger generation think about questions in different social spheres. In addition, the authors note that some projects are used in everyday life and give an example as evidence.
Жоба жұмысын жазу арқылы 11 сынып оқушыларының зерттеу дағдыларын дамыту
Развитие исследовательских навыков при написании проектной работы учащихся 11 классов
Keywords: purposefulness and systemativeness; motivation; psychological comfort; teacher's personality; creative environment; research activity; high-level skills; new approaches to training; curriculum; guidance on writing course work; evaluation criteria; form for the statement of the topic